MANAJEMEN KONFLIK INTERPERSONAL DALAM KELURGA TERHADAP STIGMA PADA DIRI SPG ROKOK DI KOTA SEMARANG - Putty Elvia Nusdalita; Wiwid Noor Rakhmad (Interaksi Online, 2020)
Working in stigma is not an easy thing to do, this is felt by women who work as SPG (Sales Promotion Girl) cigarettes, getting stigma for SPGs are considered as a risk from their profession. Cigarette SPGs examined in this study are those who still live with their families, this is done so that researchers can examine the risks that occur on the stigma felt by cigarette SPG families so that it causes interpersonal conflicts within the family in the form of complaints against the Informant profession as SPG cigarettes. This study aims to determine the type of conflict management used by SPG cigarettes in dealing with interpersonal conflict in the family over their profession, therefore the researcher uses the theory of interpersonal conflict management as a reference to theoretical criteria. The method of collecting data from this study was in-depth interviews with three cigarette SPGs domiciled in Semarang. The results of this study shows that the stigma of the SPG occurs because with the uniform and makeup attached to the body of the SPG cigarette, artifactually often gets negative responses from the public. Furthermore, this study will explore the conflict management within the SPG cigarette family over the stigma of the community. Conflicts that occur in cigarette SPG families over the stigma of their profession occur because the family does not want if their family members are considered negative by others, so that complaints arise from members of the SPG cigarette family to leave the profession. This research on conflict management groups the types of interpersonal conflict management into six categories, which are Domination, Capitulation, Inaction, Withdrawal, Negosiation and Third Party Intervenion. Based on research findings regarding interpersonal conflict management, researchers find that the type of conflict management used in dealing with problems will depend on the problem itself, because every problem that occurs will always demand its own type of conflict management. In addition, each type of conflict management if done will always pose its own risks so that this becomes a consideration of the informants to determine attitudes in dealing with interpersonal conflict within the family.